Exploring students’ concept images of fractions: A hermeneutic phenomenology study - Andriatna, Riki (Indonesian Journal of Science and Mathematics Education, 2025)
Understanding the concept of fractions is a crucial aspect of mathematics learning; however, students often develop diverse mental representations of this concept. This study aims to describe students' concept image in understanding fractions, particularly their interpretation. A qualitative approach with the hermeneutic phenomenology method was employed, where data were collected through written tests and interviews with eight selected students. Data analysis was conducted using the Constant Comparative Method (CCM), with validation through triangulation and peer debriefing. The findings reveal that students possess various concept images of fractions, including fractions as separate numbers, as numbers consisting of a numerator and denominator, as a single entity, as a part of a divided whole, and as numbers related to other mathematical concepts. However, students' understanding of their concept images remains limited, potentially leading to errors in solving fraction problems. The diversity of concept images reflects differences in students' learning experiences, highlighting the need for more varied and contextual teaching approaches in presenting fraction concepts. These findings imply the need for more effective instructional strategies to optimize students' understanding and minimize future learning barriers.